Tracing translations of ICT policies in higher education - Gary Alberto Cifuentes; Paola Valero (Arizona State University, 2016)
Educational policy enactment is a matter of policy translation. A Latourian sociomaterial perspective is proposed to challenge traditional policy implementation frameworks. We offer analytical tools to trace processes of policy translation in practice settings as entanglements of human agents, material actants and activities. The analytical strategy is deployed in the case of three Colombian higher education institutions working with ICT policies for teacher development. The cases show that agency is distributed among different entities constituting assemblages that enact policies in unexpected pathways. Equally, in all these cases routine activities or unobserved artifacts were key to trace such translations of policies. Our analysis and findings provide a critical review of hermeneutics of policies, one of the dimensions of Stephen Ball´s policy enactment theory. In doing so, a more nuanced understanding of policy enactment is achieved, contributing both theoretically and methodologically in the analysis of education policies in Latin America.